TINJAUAN YURIDIS TERHADAP PERMOHONAN PENGESAHAN PERKAWINAN YANG TIDAK DICATATKAN (ISTBAT NIKAH) - Herni Widanarti (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Every marriage in Indonesia should be based on Law No 1, 1974 of year about Marriage. But oftentimes because one/something a marriage is not booked, so a couple cannot have marriage certificate as an evidence for legal marriage that unacknowledged by country. Using normative methods, with specification writing of descriptive the analysis, the author will examine the application validation marriage that is not registered (marriage istbat). Every Judge’s consideration on accepting a request for legalization a not registered marriage (marriage istbat) is based on provision Article 7 paragraph (3) letter (e) Kompilasi Hukum Islam (KHI). Keywords : marriage, not registered marriage, legalization of marriage that is not registered (Marriage Istbat) Abstrak Setiap perkawinan di Indonesia harus tunduk kepada Undang-Undang Nomor 1 tahun 1974 tentang Perkawinan. Namun seringkali karena sesuatu hal, perkawinan tidak dicacatkan sehingga tidak mempunyai akta nikah sebagai bukti sahnya perkawinan yang diakui oleh negara. Dengan menggunakan metode yuridis normatif, dengan spesifikasi penulisan deskriptif analisis, penulis akan menelaah permohonan pengesahan perkawinan yang tidak dicatatkan (itsbat nikah). Setiap pertimbangan Hakim dalam mengabulkan permohonan pengesahan perkawinan yang tidak dicacatkan (istbat nikah) adalah berdasarkan ketentuan Pasal 7 Ayat (3) huruf (e) Kompilasi Hukum Islam (KHI). Kata Kunci : Perkawinan, Perkawinan Tidak Dicatatkan, Pengesahan Perkawinan yang Tidak Dicatatkan (Istbat Nikah).